Influence of site and smoking on malignant transformation in the oral cavity: Is the microbiome the missing link? - Galvin, Sheila; Moran, Gary P.; Healy, Claire M. (Frontiers in Oral Health, 2023)
The tongue and floor of mouth are high risk sites for oral squamous cell carcinoma (OSCC), while smoking is its most significant risk factor. Recently, questions have been raised as to the role of the oral microbiome in OSCC due to a wealth of evidence demonstrating that the microbiome of OSCC differs to that of healthy mucosa. However, oral site and smoking also have a significant impact on oral microbial communities and to date, the role these factors play in influencing the dysbiotic microbial communities of OSCC and precursor lesions has not been considered. This review aims to examine the influence of site and smoking on the oral microbiome and in turn whether these microbiome changes could be involved in oral carcinogenesis.